Commerce Matriculants: Gender and Ability - Keef, S.P (School of Management Working Papers, 1990)
The gender and qualifications of matriculants entering the Faculty of Commerce and Administration were compared with those entering the rest of the University. The results show that the Faculty has, over the past ten years, attracted students of lower ability than the rest of the University. Whereas females have equal representation at the University, it is apparent that the proportion of females in the commerce faculty lags some years behind the rest of the University. However, there is evidence that both differentials were declining.